The influence of small additions of Ni, Ti and C on the oxidation behaviour of sputtered tungsten coatings - Louro, C. (1999)
The oxidation rate of sputtered tungsten-based coatings, oxidised in air at temperatures of 600°C-800°C can be influenced significantly by the addition of small amounts of nickel, titanium and carbon. The presence of carbon does not change the type of oxide phases formed during the oxidation of sputtered W coatings: there are two oxide layers, the inner being a compact sub-oxide of WOx type and the outer being a typical porous WO3 phases. The addition of Ni and Ti, however gives rise, in addition to WOx and WO3, of other type of oxides, such as NiWO4 and TiO2, respectively. The oxidation process is very complex, with different fluxes of species to be considered: the oxygen ion flux from the exterior to the interior, and Ni and Fe diffusing towards the exterior. At the annealing temperature of 800°C, in the cases of W-C-Ni films, a FeWO4 layer is detected beneath the mixed oxide. The greatest oxidation resistance is obtained for W-C-Ti, followed by W-C-Ni and finally W-C.